SHIFTS IN LEAF PHENOLOGY OF THREE HIMALAYAN OAK SPECIES: ROLE OF WOOD WATER PROPERTIES - Chand, Deepak B.; Poudyal, Kanta; Jha, P. K. (Ecoprint: An International Journal of Ecology, 2017)
An investigation has been done with the three Himalayan oak species at Phulchowki Hill Lalitpur Nepal to relate leaf phenology responses of trees to wood water properties. We recorded the wood water content, wood density, water in wood and leaf phenological patterns of three evergreen oak species (Quercus semecarpifolia, Quercus lamellosa and Quercus glauca) for 2 years. Our results revealed significant changes in leaf phenology within oak species between years, with shifts in leaf emergence, leaf damage and leaf senescence. Shifts in tree leaf phenology found in studied years suggest that the inter-annual and monthly variation in wood water properties could attribute to shift in tree leaf phenology. ECOPRINT 24: 29-36, 2017